Omega-3 Fatty Acids and Depressive Symptomology and the Influence of Psychosocial Stress: The Hispanic Community Health Study/Study of Latinos. (29th May 2020) - Porter, Caitlin; Karazurna, Nicole; Aytur, Semra; Morrell, Jesse; Mossavar-Rahmani, Yasmin; Tamez, Martha; Mattei, Josiemer; Perreira, Krista; Sotres-Alvarez, Daniela; Gallo, Linda; Daviglus, Martha; Isasi, Carmen; et al.
Abstract: Objectives: The literature on n -3 fatty acid (FA) intake and depressive symptoms is inconsistent, potentially due in part to the influence of psychosocial stress. Some evidence supports that n -3 intake may have greater benefit on depressive symptoms among those with high oxidative stress. We quantified the associations between dietary and plasma n -3 FA and 6-y depressive symptoms and measured the modifying effect of psychosocial stress. Methods: Data are from the Hispanic Community Health Study/Study of Latinos (age 48 y, 63% female). At baseline (2008–11), EPA, DHA and n -3 very-long-chain FAs ( n- 3VLCFAs) were estimated using two 24-hr recalls and the NCI method. Plasma n -3 FAs were measured by mass spectrometry. Depressive symptoms were measured at baseline and 6-y follow-up with the 10-item Center for Epidemiological Studies Depression Scale (CESD). Approximately 9 months from baseline, the 10-item Perceived Stress (PSS) and Chronic Burden of Stress scales were obtained. Unstratified and psychosocial stress-stratified associations were analyzed using survey linear regression among those with dietary ( n = 3537) and plasma ( n = 718) FA data. Model covariates included, but were not limited to, baseline CESD score, ethnicity, study site, antidepressant use, total energy intake, and dietary or plasma n -6 FA. Results: Baseline DHA and n-3VLCFA intake were inversely associated with 6-y CESD ( P < 0.05). All examined dietary n-3 FA exposures were inversely associated with CESD among those in the highest PSS quartile (Q4) ( P < 0.05), but this was attenuated after considering n-6 FA intake. DHA and n-3VLCFA intakes were associated with lower CESD among those with 2 chronic stressors, but not <1 or >2 stressors. Plasma n-3 FAs were not associated with CESD in PSS stratified and unstratified analyses. However, plasma n-3 FA were associated with lower CESD score among those with only 2 chronic stressors. Conclusions: Dietary n -3VLCFAs, but not plasma, were inversely associated with 6-y CESD. Psychosocial stress did not clearly modify these associations. These results provide some evidence that greater n -3VLCFA intake may reduce depressive symptoms among Hispanic/Latino adults. However, considering the limitations of self-reported intake, further research is needed using biomarkers of long-term n -3 consumption and psychosocial stress to confirm our findings. Funding Sources: None.